TINJAUAN SYARIAH TENTANG PEMBIAYAAN BERMASALAH DI PERBANKAN SYARIAH - Kolistiawan, Budi (An-Nisbah: Jurnal Ekonomi Syariah, 2014)
In Islamic banking fnancial institutions, fnancing is a very big asset that the funding should be maintained based on the quality of the precautionary principle. The precautionary principle is Bank management guideliness that must be adhered,  in order to create a sound, robust and effcient in accordance with the provisions of the legislation. Application of the precautionary principle by Islamic banks one of which is manifested in the analysis is to analyze the fnancing of confdence in the willingness and ability of prospective clients to settle all its obligations in time, before the Islamic Bank disburses funds to customers Recipient Facility“. The confdence gained from assessment against characteristic carefully, capability, capital, collatera, and business prospects of the receiving facility prospective customers (character, capacity, capital , collateral, condition).  Islamic banks  provide fnancing hope that funding is running smoothly, customers comply with what was agreed in the agreement and paid when due. But it can happen in the fnancing period fnancing problems arise. The efforts made by the Islamic Bank to deal with the problem of fnancing the rescue fnancing problems with restructuring efforts if the customer still has a good faith within the meaning still want to be invited to cooperate in the effort to rescue fnancing problems , but if the customer has not acting in good faith in the sense of cooperative in an effort to rescue the troubled fnancing Islamic bank will make solving the fnancing problems.Keywords : Financing, Islamic Banking, 5C